Understanding the Silent Struggles: The Lived Experiences of Single Fathers - Capacio, Leadean Jay; Mier, Kimberly Jean B.; Superales, Jul Rhea A.; Falcon, Eileen B.; Miñoza, Johanna; Dayundunan, Ianthe Mae; Siacor, Jedu; Omandam, Mary Jane (Edukasiana: Jurnal Inovasi Pendidikan, 2024)
This study explored the lived experiences of Single Fathers. Peculiar experiences like causes of broken marriages, struggles in raising their children, strategies in managing struggles, and future plans for their families were highlighted. Phenomenological approach was utilized to extract meanings from the participants’ constructs. Transcripts were analyzed using the Moustakas’ (1994) 8-step procedure. The SFs’ broken marriages are caused by infidelity, economic challenges, abuse of substance, and differences of religious belief. The SFs were burdened with fulfilling and managing multiple responsibilities, and attending to financial obligations. The SFs’ unwavering faith to the Almighty, their humbleness, and genuine love for their children enabled them to navigate the challenges of single parenthood. The SFs look forward to prioritizing the educational plan for their children, and developing themselves to become worthy and ready of building a complete and united family. The essence of the phenomenon is: The Single Fathers shouldered a heavy burden of responsibilities and financial obligations, and while raising their children alone, they drew strength from unwavering faith, humility, and a deep-seated love for their children, and planned to prioritize their children’s education and personal development in pursuit of rebuilding a complete and united family once again.